Analysis of Factors Affect the Differences of the Determination of Fajr Ṣādiq and Its Relevance to the Basic Principles of Sharia - Sirajuddin, Sirajuddin; Azwar, Azwar; Aswar, Aswar (Kawanua International Journal of Multicultural Studies, 2023)
This study aims to: (1) analyze the factors that cause differences in the determination of the beginning of fajr prayer time; (2) analyze the relevance of the determination of fajr ṣādiq as the beginning of fajr prayer time with the basic principles of Islamic law. This research is qualitative descriptive research using library research methods with normative of sharia and philosophical approach. The results of the study found several things. First, the difference in setting the schedule of fajr prayer is due to differences in the determination of the criteria of the elevation of the sun under the horizon and differences in interpreting the meaning of the naṣ and terms related to the time of fajr prayer, such as fajr, galas, isfār, tabayyun and others. Second, the basic principle in determining the beginning of the time of fajr prayer based on the perspective of Sharia is that the fajr prayer is determined by the signs that are believed, so that the criteria for the appearance of fajr ṣādiq are set at the unquestioned elevation of the sun and with signs that are ḥissiyah (observable with five senses) in accordance with maqāṣid al-taysīr that can be understood and observed by every Muslim. This study contributes to the studies related to determining the start of prayer times. The results of this study provide recommendation in the form of determining the angle of fajr ṣādiq at the criterion between -18º and iḥtiyāṭ 2 minutes or -17.5º, as a precautionary measure, so that the polemic that occurs in the community regarding prayer time schedules is expected to be reduced or even resolved.